A Study to investigate whether Perceptions of Adolescent Alcohol Consumption and Binge Drinking have changed over time. - Mohan, Catherine (2008)
Background According to Plant and Plant (1992), adolescent alcohol consumption is seen as important rites of passage into adulthood due to the "wet culture" young people are brought up in in England. However, Honess, Seymour and Webster (2000) argue that adolescent alcohol consumption has moved beyond imitating adult behaviour and is as much a "normal" behaviour as adult alcohol consumption. This has lead to concern regarding the health of adolescents. This study aimed to look at whether adolescent perceptions of alcohol have changed over time and if so, whether societal changes in the construction of adolescence may have been influential in changing perceptions. Findings from the study were used to make suggestions regarding future nursing practice and Government policy aimed at changing adolescent perceptions of alcohol.